Frequency and Risk Factors of Adenomyosis in Women Undergoing Hysterectomy at Benghazi Medical Center - Fawzia Alharari; Asma Belrawin; Bouzaid, Najwa (AlQalam Journal of Medical and Applied Sciences, 2025)
Adenomyosis is a non-malignant disorder characterized by the infiltration of endometrial tissue into the myometrium, resulting in an enlarged, soft uterus. It may be asymptomatic or manifest symptoms, including abnormal uterine bleeding, dysmenorrhea, pelvic discomfort, and, less frequently, dyspareunia. A physical examination frequently indicates a painful, diffusely enlarged uterus. To ascertain the prevalence and risk factors of adenomyosis in patients having hysterectomy at Benghazi Medical Center (BMC). A descriptive case series study was conducted over one year, from June 2023 to December 2023, at the Benghazi Medical Center. The study includes all women admitted to the Obstetrics and Gynecology Department who undergo a hysterectomy, regardless of indication, during the specified study period. Adenomyosis was diagnosed histopathologically in 19.2% of cases. Among these, 40% had coexisting uterine leiomyoma; a statistically significant association was found (p = 0.047). Women with adenomyosis had a higher mean parity (4.6 vs. 4.0). Hormonal therapy use has a significant association with adenomyosis (p = 0.001), potentially reflecting prior symptomatic treatment or a link with disease modulation, and pelvic pain is significantly associated (p = 0.032), suggesting it may be a more specific symptom of adenomyosis.